2009
DOI: 10.1183/09031936.00171507
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutases, lung function and bronchial responsiveness in a general population

Abstract: Oxidative stress is an important causative factor in the onset and progression of smoking-related lung diseases, such as chronic obstructive pulmonary disease (COPD). Superoxide dismutases (SODs) can prevent an increase in oxidative burden.A total of 1,390 subjects from the prospective Vlagtwedde-Vlaardingen cohort were genotyped for two single nucleotide polymorphisms (SNPs) in SOD2 and four SNPs in SOD3, which were further analysed for associations with the presence of bronchial hyperresponsiveness (BHR; pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
0
32
1
Order By: Relevance
“…In children, we found that SOD3 singlenucleotide polymorphisms (SNPs) were associated with decreased FEV 1 and maximal expiratory flow at 25% volume (22). In adults, SOD3 SNPs have been associated with lower lung function (24,25) and increased risk of developing chronic obstructive pulmonary disease (COPD) (26). These findings support the rapid identification of candidate genes in mice that can later be tested in human populations.…”
Section: Introductionmentioning
confidence: 68%
“…In children, we found that SOD3 singlenucleotide polymorphisms (SNPs) were associated with decreased FEV 1 and maximal expiratory flow at 25% volume (22). In adults, SOD3 SNPs have been associated with lower lung function (24,25) and increased risk of developing chronic obstructive pulmonary disease (COPD) (26). These findings support the rapid identification of candidate genes in mice that can later be tested in human populations.…”
Section: Introductionmentioning
confidence: 68%
“…Included in this set were: SERPINA1 (Fig. 7A), the gene that encodes for ␣1 antitrypsin, a major genetic cause of emphysema in humans (62); EDN2, whose disruption causes emphysema in mice (63); SOD2, which protects the airway epithelium from oxidative damage (64,65); SERPINA3, which encodes the ␣1 anti-chymotrypsin gene, a potent inhibitor of mast cell proteases that is implicated in asthma pathogenesis (66,67); FOXP4, which represses goblet cell differentiation and mucus secretion (68); and ABR (Fig. 7A), a RAC inhibitor whose deficiency worsens airway hyperresponsiveness and inflammation in murine allergic asthma models (69).…”
Section: Gr Occupancy Patterns and Repression Of Tnf Targetmentioning
confidence: 99%
“…1,2 The presence of BHR can be assessed by a bronchial challenge test with methacholine or histamine. The prevalence of BHR in the general population is generally thought to be 10-25% and is dissimilar between studies.…”
mentioning
confidence: 99%